Myocardial infarction after noncardiac surgery in Sweden: a national, retrospective observational cohort study. (July 2020) - Hallqvist, Linn; Granath, Fredrik; Bell, Max
Abstract: Background: The precise incidence of perioperative myocardial infarction (MI) after noncardiac surgery remains unclear. We determined the incidence and risk factors for perioperative MI after noncardiac surgery and the risk of MI and mortality compared with matched non-surgical patients. Methods: Patients >18 yr undergoing noncardiac surgery in 23 Swedish hospitals from 2007 to 2014 were included in this national observational retrospective cohort study. We combined national surgical and outcome databases with Swedeheart, a national quality registry capturing data from patients with acute MI. The primary outcome was incidence of MI within 30 days of surgery. Multivariable logistic regression identified preoperative risk factors associated with MI, including ASA grade, diabetes mellitus, and cardiovascular pathology including previous MI. Standardised incidence rate ratios were calculated. Mortality rates were estimated using Cox proportional hazards. Results: A total of 1605/400 742 (0.41%) patients (median age: 64 [49–75] yr) had an MI after surgery, which was independently associated with increasing age, comorbidities and higher risk (vascular, thoracic), emergency surgery, or all. The incidence of perioperative MI (per 1000 surgeries) varied from 0.064 (95% confidence interval [CI], 0.02–012) in low-risk patients (ASA physical status 1) to 15.8 (95% CI, 14.9–16.8) among higher risk patients (ASA physical status ≥3, age ≥80 yr, high-risk surgery). Perioperative MI was associated with higher 30-day mortality (adjusted odds ratio: 5.49 [95% 4.76–6.32]). Compared with the non-surgical Swedish population, the perioperative standardised incidence rate ratio was five-fold higher (odds ratio: 5.35 [95% CI: 5.09–5.61]). Conclusions: In a large Swedish surgical cohort, the incidence of MI within 30 days of noncardiac surgery was 0.41%, chiefly occurring in a small subset of higher risk patients.